Combination of organic acids and low-dose gamma irradiation as antimicrobial treatment to inactivate Shiga toxin-producing Escherichia coli inoculated in beef trimmings: Lack of benefits in relation to single treatments - Cap, Mariana; Cingolani, Celeste; Lires, Carla; Mozgovoj, Marina Valeria; Soteras, Trinidad; Sucari, Adriana; Gentiluomo, Jimena; Descalzo, Adriana Maria; Grigioni, Gabriela Maria; Signorini, Marcelo; Horak, Celina; Vaudagna, Sergio Ramon; et al. (Plos ONE, 2020)
The aim of this study was to assess the efficacy of lactic acid (LA), caprylic acid (CA), high- (HDI) and low- (LDI) dose gamma irradiation and LDI combined with LA or CA on the inactivation of a pool of Shiga toxin-producing Escherichia coli (STEC) strains inoculated on beef trimmings. The three most efficacious treatments were selected to study their effect on meat quality parameters and sensory attributes. The inoculum included five native STEC serogroups (O26, O103, O111, O145 and O157). The treatments applied were 0.5% LA, 0.04% CA, 0.5 kGy LDI, 2 kGy HDI, LDI+LA and LDI+CA. Beef trimmings were divided into two groups; one was inoculated with high (7 log CFU/g) and the other with low (1 log CFU/g) level of inoculum. Efficacy was assessed by estimating log reduction and reduction of stx- and eae-positive samples after enrichment, respectively. Results showed that treatments with organic acids alone were not effective in reducing STEC populations. For high inoculum samples, the most effective treatment was HDI followed by LDI+LA and LDI alone or combined with CA. For low inoculum samples, the most effective treatment was HDI followed by LDI alone or combined with organic acids. Concerning meat quality parameters and sensory attributes, irradiation treatments (LDI and HDI) caused minimal changes, while LDI+LA modified them significantly compared with the control. Therefore, based on our results, no benefits were observed after combining organic acids with gamma irradiation.